Agility in the Swedish intermodal freight market – The effects of the withdrawal of the main provider. (June 2017) - Flodén, Jonas; Woxenius, Johan
Abstract: Based on interviews and two workshops with the main stakeholders as well as media coverage, this article analyses the changes in the market from the deregulation leading up to the Swedish market exit of CargoNet, the former monopolist provider of intermodal freight transport, and the events that followed. The analysis applies business model theory. When CargoNet left the Swedish market in April 2012, some of the traffic was absorbed by other intermodal providers and the wagon load rail system. The routes to the far north of Sweden, however, were assuming an infrastructure role for the main forwarders and road hauliers, who formed the joint venture Real Rail with CargoNet to continue traffic. The business model applied by Real Rail differed from CargoNet's and other intermodal providers, mainly by the tight connection to the customers, who guaranteed volumes.